EFA Analysis of Online Learning Success in Elementary Schools: Exploratory Study in Schools with International Curriculum - Habibi, M. (DPPM Universitas Pelita Bangsa, 2025)
This study was motivated by the many variables that influence the success of online learning in elementary schools. Therefore, this study aims to extract these variables to produce several main factors that can explain all the variance. This study is quantitative, adopting a multivariate statistical approach with Exploratory Factor Analysis (EFA). The research subjects were 108 teachers from Al Azhar 32 Islamic Elementary School, Telkom Elementary School, Yari International School, and SafaMarwa Islamic International School. From the opinion survey, 23 variables were obtained that influenced the success of online learning in elementary schools. After going through a series of EFA analysis procedures, 20 variables were successfully extracted into 8 main factors, namely: (1) Psychological Readiness and Self-Regulation (3.152), (2) Digital Learning Technology Support (2.264), (3) Pedagogical and Professional Competence of Teachers (1.663), (4) Quality of Learning Design and Materials (1.426), (5) Teachers' Instructional Communication (1.313), (6) Home Learning Environment Support (1.303), (7) Teacher and Student Technology Capabilities (1.054), and (8) Student Social and Academic Participation (1.030).